1990
DOI: 10.1007/bf01740939
|View full text |Cite
|
Sign up to set email alerts
|

Active specific immunotherapy with vaccinia colon oncolysate enhances the immunomodulatory and antitumor effects of interleukin-2 and interferon α in a murine hepatic metastasis model

Abstract: The role of cytokines as primary or adjuvant antineoplastic agents has been well established. Interleukin-2 (IL-2) and the interferons have, particularly, proven to be effective antitumor agents when given alone, and seem to act synergistically on the eradication of metastases from immunogenic tumors. Active specific immunotherapy, in the form of viral oncolysates, has also shown effectiveness in cancer therapy. Bearing this in mind, we decided to combine these agents in an adjuvant triple regimen and compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Viral oncolysates have been utilized to increase whole tumor cell vaccine immunogenicity, which can be mediated through DC activation by "danger signals" released by virally infected tumor cells, or via increased uptake of tumor lysate by DCs due to viral ligands expressed on the surface of virally infected tumor cells, which may engage additional receptors on DCs [66][67][68][69][70] [74]. A phase II clinical trial of NDV-modified autologous tumor cells in 63 patients with advanced breast and ovarian cancers disease also showed a benefit in survival (P = 0.026) and disease-free survival (P = 0.089) [75].…”
Section: Infection Of Whole Tumor Cells With Inactivated Virusesmentioning
confidence: 99%
“…Viral oncolysates have been utilized to increase whole tumor cell vaccine immunogenicity, which can be mediated through DC activation by "danger signals" released by virally infected tumor cells, or via increased uptake of tumor lysate by DCs due to viral ligands expressed on the surface of virally infected tumor cells, which may engage additional receptors on DCs [66][67][68][69][70] [74]. A phase II clinical trial of NDV-modified autologous tumor cells in 63 patients with advanced breast and ovarian cancers disease also showed a benefit in survival (P = 0.026) and disease-free survival (P = 0.089) [75].…”
Section: Infection Of Whole Tumor Cells With Inactivated Virusesmentioning
confidence: 99%
“…The murine colon cancer cell line CC-36 [14], human fibroblast cell line MRC5, monkey kidney cell line VERO (ATCC, Bethesda, MD), and the NK sensitive cell line YAC-1 were used in the described experiments.…”
Section: Cell Linesmentioning
confidence: 99%
“…This led to the development of a variety of viral oncolysates for use in clinical trials for many different cancers, including ovarian cancer [170][171][172]. Clinical experimentation with viral oncolysate vaccines has shown that antitumour immune responses may be elicited in select patients.…”
Section: Whole Tumour Antigen Vaccinesmentioning
confidence: 99%